Child labor, rainfall shocks, and financial inclusion: Evidence from rural households - Carolina Bernal; Razvan Vlaicu (Inter-American Development Bank (IDB), 2023)
This paper examines how rural households cope with climate change related rainfall shocks by re-allocating children's time between domestic activities and school attendance. Households affected by an unanticipated rainfall shock face an inter-temporal trade-off between current household income and future potential earnings. Financial inclusion may mitigate or exacerbate the human capital impacts of rainfall shocks depending on whether it relaxes or constrains household budgets. The data come from a three-round panel household survey in rural Colombia collected between 2010-2016. The main findings are that rainfall shocks induce households to choose immediate benefits over long-run investments in education by increasing the incidence of child labor and household chores at the expense of school attendance. Over-indebtedness through pre-existing formal loans reinforces the likelihood that a child works due to rainfall shocks, whereas asset insurance, foreign remittances, and natural disaster aid mitigate or eliminate the shock-induced shift toward domestic activities and away from schooling.
Keywords: D14; J13; J22; O15; Q54; 330; Child labor; Human capital; Rainfall shocks; Climate change; Financial inclusion; Rural households